1998
DOI: 10.1002/hep.510270104
|View full text |Cite
|
Sign up to set email alerts
|

Variceal pressure is a factor predicting the risk of a first variceal bleeding: A prospective cohort study in cirrhotic patients

Abstract: Predictive criteria for a first variceal hemorrhage lack substantial accuracy. Cross-sectional studies suggest a close relationship between variceal pressure (VP) and the occurrence of variceal bleeding. In the present prospective cohort study, the significance of VP measurement for prediction of a first variceal bleed was assessed. Eighty-seven patients with cirrhosis and large esophageal varices who had never developed variceal bleeding were followed for 12 months. The endpoint of the study was the presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 26 publications
(38 reference statements)
2
67
0
Order By: Relevance
“…31 In this study, variceal pressure was measured using a noninvasive technique developed in our laboratory that has been validated in other centers also. [15][16][17]32 This technique, however, has some limitations. The first and more important is that it is not feasible in every patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 In this study, variceal pressure was measured using a noninvasive technique developed in our laboratory that has been validated in other centers also. [15][16][17]32 This technique, however, has some limitations. The first and more important is that it is not feasible in every patient.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 The transmural pressure at the varices can be assessed noninvasively at endoscopy using a pressure-sensitive endoscopic gauge developed in our laboratory that has been shown to allow accurate, reproducible measurements of variceal pressure. [9][10][11][12][13][14][15][16][17] Previous studies indicated that the technique allows assessment of the acute and chronic effects of drug therapy on portal hypertension. 11-15 Moreover, there is evidence suggesting that measurements of variceal pressure may have prognostic value in Abbreviations: TIPS, transjugular intrahepatic portosystemic shunt; HVPG, hepatic venous pressure gradient; WHVP, wedged hepatic venous pressure; FHVP, free hepatic venous pressure; CI, confidence interval; ROC, receiver operating characteristic curve; NIEC, North Italian Endoscopic Club index.…”
mentioning
confidence: 99%
“…The risk of variceal bleeding is highly dependent on portal pressure. 74 It is now accepted that associated coagulopathy whether related to the underlying liver disease or anticoagulant use does not precipitate variceal bleeding, but can make the bleeding more severe. In published studies, the overall incidence of bleeding complications with anticoagulant use in cirrhotics has been reported to vary from 5% to 35%.…”
Section: Complications Of Anticoagulation and Prophylaxis Of Varicealmentioning
confidence: 99%
“…Large esophageal varices (LEV) are at a greater risk, which is possibly due to a higher variceal wall tension [7] . Availability of non-invasive methods for detection of LEV may help limit the number of endoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%